PENGARUH GAYA KEPEMIMPINAN DIGITAL, PENGEMBANGAN KARIER DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI : THE INFLUENCE OF DIGITAL LEADERSHIP STYLE, CAREER DEVELOPMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT - Rantauwati, Ervina Agustin; Zulkifli Zulkifli; Putriana, Lies (Jurnal Riset Manajemen dan Akuntansi, 2022)
This study aims to find the effect of the independent variables on the dependent variable through intervening variables. The sample in this study is partly the number of PNS Litbangkes employees 304 people. There are five types of variables that will be used in this study: digital leadership style (X1), career development (X2), organizational culture (X3), performance (Y) and organizational commitment (Z). This study uses SEM analysis and AMOS application with a quantitative approach through distributing questionnaires with 50 statements of research results, it can be concluded: (1) There is a significant influence between the independent variable Digital Leadership Style (X1) on the variable Employee Performance (Y) through the Intervening variable ( Z) Organizational Commitment, (2) there is a significant influence between the independent variable Career Development (X2) on the variable Employee Performance (Y) through the Intervening variable (Z) Organizational Commitment (3) there is a significant influence between the independent variable Organizational Culture (X2) on devenden variable (Y) Employee Performance through Intervening variable (Z) Organizational Commitment.